Effectiveness of Leaflet Media on Mother's Interest in Information on Balanced Nutrition for Toddlers - Desy Winda; Anggy Trisnadoli (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Unbalanced food consumption in toddlers can lead to serious health issues like malnutrition. Leaflets can be used as a tool to increase mothers' knowledge about balanced nutrition for their toddlers. The purpose of this study was to evaluate the effectiveness of leaflets in improving mothers' knowledge and interest in balanced nutrition for their toddlers in Kampung Baru, Riau Province. This research employed a Quasi Experiment with the One Group Pre-Post Test design and involved 85 respondents of mothers with toddlers in Kampung Baru Village. The study utilized the purposive sampling technique, collected data through a questionnaire, and performed univariate and bivariate analysis using statistical tests. The findings indicate that the P-value = 0.000, demonstrating the effectiveness of leaflets in increasing mothers' interest in balanced nutrition for their toddlers. As a result, health workers are encouraged to educate and provide information about balanced nutrition for toddlers through counseling and distribute leaflets more actively in Kampung Baru, Riau Province.